Effect of yeast probiotic Saccharomyces cerevisiae on the gut health of dogs undergoing rapid dietary transition - Xu, Jia; Wen, Chaoyu; Song, Guangming; Lesaux, Achraf Adib; Zhang, Hao; Luo, Yu (Frontiers in Microbiology, 2025)
IntroductionRapid dietary transition in dogs can disturb the balance of gut microbiota, resulting in symptoms such as diarrhea and compromised immune function. Yeast probiotic (Saccharomyces cerevisiae), has been shown to improve intestinal microbial composition and stimulate immune function. This study aims to investigate the effects of yeast probiotic Saccharomyces cerevisiae supplementation on hematology, serum biochemistry, fecal IgA, microbiota, and metabolites in dogs undergoing rapid dietary transition.MethodsTwenty healthy adult dogs were allocated into two groups: the control group (CON) and the yeast probiotic supplementation (YPS). All dogs were initially fed Diet 1 for 4 weeks, followed by an abrupt switch to Diet 2 for another 4 weeks. Throughout the study, the YPS group received 0.1% Actisaf® Sc 50 product in a capsule given with their food, while the control group received a placebo.ResultsCompared to the CON group, the YPS group exhibited lower serum globulin levels and higher albumin-to-globulin ratios on days 28 and 56 (p < 0.05). On day 56, the YPS group showed lower white blood cell counts and lower serum glucose levels (p < 0.05). Fecal IgA concentrations were higher in the YPS group on days 28, 30, 42, and 56 (p < 0.05). In the CON group, the abundance of Firmicutes significantly increased and the abundance of Fusobacteriota and Bacteroidota significantly decreased on days 42 compared to day 28 (q < 0.05). The YPS group showed a more stable gut microbiota transition post-dietary change. In the CON group, no significant changes in metabolite composition were observed 2 days after the dietary transition, but notable changes appeared after 2 weeks. In contrast, the YPS group exhibited substantial changes in metabolite composition 2 days after the diet change. Tyrosine metabolism showed significant changes in both groups of dogs following the dietary transition.ConclusionSaccharomyces cerevisiae supplementation during rapid dietary transition in dogs led to beneficial changes in blood parameters, increased fecal IgA levels, and promoted a more stable gut microbiota. These findings suggest that yeast probiotics may support gut health and immune function during periods of dietary change.